Linguistic Competence in Quechua through Dialogue: An Intercultural Educational Proposal - Rojas -Tello, Luis; Huarcaya - Barbarán, Anatolio; Rivera - Fuentes, Wilmer; Poma – Solier, Teodosio; Yacca – Poma, Heber (Journal of Ecohumanism, 2025)
The objective of the research was to analyze the pedagogical experiences of teachers who teach the Quechua language in rural contexts of Huamanga. Through the qualitative approach with in-depth interviews conducted with six teachers specialized in Quechua, we sought to understand communicative competencies through intercultural dialogue in secondary educational institutions. The methodology used consisted of semi-structured interviews, with a script designed to obtain detailed information on teachers’ perceptions and pedagogical practices. The interviews were transcribed and subsequently processed using Microsoft Visio and Atlas Ti, which allowed a systematic organization and analysis of the data. The results of the research revealed that teachers use various pedagogical strategies to promote the learning of Quechua, highlighting the importance of intercultural dialogue in the classroom. In conclusion, it was identified that the intercultural approach is fundamental to strengthen communicative competencies in Quechua, and the need to implement innovative methodologies that favor the significant learning of the language in rural contexts was proposed.